2010
DOI: 10.1111/j.1439-0418.2010.01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Mating compatibility among Bactrocera cucurbitae (Diptera: Tephritidae) populations from three different origins

Abstract: Distinct host ranges of the melon fly, Bactrocera cucurbitae (Coquillett), have been reported among different island populations, suggesting significant genetic divergence. Thus, for the application of the sterile insect technique (SIT), it is important to ensure that released flies are sexually fully compatible with each other and with the laboratory strains. Mating tests among the following strains of the melon fly, B. cucurbitae: Mauritius laboratory‐adapted (35 generations), Seychelles laboratory‐adapted (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…However, the success of large scale (international/inter-continental) SIT programme depends on the mating compatibility of the released laboratory strain with the wild flies. To support the above phenomenon, mating tests among three B. cucurbitae populations from Mauritius, Seychelles and Hawaii (genetic sexing strain) were conducted by Sookar et al (2010) and they observed that the sexual activity among the three melon fly populations was similar as non significant non-random, assortative mating was observed. Therefore, they concluded that melon flies from Mauritius, Seychelles and the Hawaii are compatible, at least under semi-natural conditions.…”
Section: Discussionmentioning
confidence: 70%
“…However, the success of large scale (international/inter-continental) SIT programme depends on the mating compatibility of the released laboratory strain with the wild flies. To support the above phenomenon, mating tests among three B. cucurbitae populations from Mauritius, Seychelles and Hawaii (genetic sexing strain) were conducted by Sookar et al (2010) and they observed that the sexual activity among the three melon fly populations was similar as non significant non-random, assortative mating was observed. Therefore, they concluded that melon flies from Mauritius, Seychelles and the Hawaii are compatible, at least under semi-natural conditions.…”
Section: Discussionmentioning
confidence: 70%
“…Zeugodacus cucurbitae has been considered a major pest species of commercially grown cucurbits in large parts of Asia (Kapoor 1989, Koyama 1989) and Hawaii (Harris 1989) for a long time. However, in the Afrotropical region, not much research was devoted to this species in comparison to other cucurbit infesting dacines, except for La Réunion (White and Elson-Harris 1994, Vayssières 1999, Ryckewaert et al 2010) and Mauritius (Sookar et al 2012, 2013). This is currently changing due to the recent observations on its distribution and dominance in particular crops (see below under ‘host range and interspecific competition’).…”
Section: Distribution Origin and Population Structurementioning
confidence: 99%
“…Sookar et al (2013) looked at the mating compatibility between populations of Mauritius, the Seychelles and Hawaii but only found random, non-assortative mating between the populations. Within La Réunion, Jacquard et al (2013) also described the occurrence of local genetic clusters with distinct distributions across the eastern and western coast of the island.…”
Section: Distribution Origin and Population Structurementioning
confidence: 99%
“…Cross-mating experiments were conducted at the start of the CRP between populations of Mauritius, Seychelles and a genetic sexing strain of Hawaii and these indicated no mating incompatibility or sexual isolation (Sookar et al 2013). Given this fact and the genetic assessments, it was decided there was no need for additional cross-mating studies.…”
Section: Situation Analysis At the Start Of The Crp And Ouputs For Eamentioning
confidence: 99%